2019
DOI: 10.1177/0309364618824443
|View full text |Cite
|
Sign up to set email alerts
|

The effect of knee brace misalignment on the anterior cruciate ligament

Abstract: Background: Protective knee braces are used for rehabilitation or prevention. Due to poor patient compliance or slippage, the brace might be misaligned with the knee axis. Objectives: Does a misaligned knee brace stress the anterior cruciate ligament? Study design: It is an experimental study. Methods: A strain sensor was implanted on the anterior cruciate ligament in eight limbs. The limbs were mounted in a knee simulator, muscle forces were applied and a cyclic motion from 10° to 60° flexion was performed un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In those studies, the braces were worn by human subjects and not actuated through any external force application. A cadaver study found that while the well-aligned brace reduced the strain on the anterior cruciate ligament, the misaligned situation showed an increased strain compared to the unbraced knee [ 16 ]. Despite the difference in research question and approach, with the present study using this passive knee brace to simulate a powered exoskeleton, the findings of the cadaver study are along similar lines as our outcome of an increasing joint load with increasing misalignment.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, the braces were worn by human subjects and not actuated through any external force application. A cadaver study found that while the well-aligned brace reduced the strain on the anterior cruciate ligament, the misaligned situation showed an increased strain compared to the unbraced knee [ 16 ]. Despite the difference in research question and approach, with the present study using this passive knee brace to simulate a powered exoskeleton, the findings of the cadaver study are along similar lines as our outcome of an increasing joint load with increasing misalignment.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, the braces were worn by human subjects and not actuated through any external force application. A cadaver study found that while the well-aligned brace reduced the strain on the anterior cruciate ligament, the misaligned situation showed an increased strain compared to the unbraced knee [208]. Despite the difference in research question and approach, with the present study using this passive knee brace to simulate a powered exoskeleton, the findings of the cadaver study are along similar lines as our outcome of an increasing joint load with increasing misalignment.…”
Section: Discussionsupporting
confidence: 74%
“…Cadaver studies can also be a means to assess effects of physical human-robot interaction on biological structures such as ligaments. Limitations of such an approach can be the limited muscle forces and different behavior of tissues compared to living human tissue [208].…”
Section: The Future Of Safety Assessments In Physical Human-robot Int...mentioning
confidence: 99%
“…Some nonsurgical options include the usage of a brace to increase knee stability and physical therapy to rehabilitate knee function and strength (39). Evidence indicates that ACL strains can be minimized with the use of a correctly positioned knee brace in comparison with an unbraced knee; a misplaced brace seems to increase the risk of ACL strain (39). Current functional bracing solutions do not sufficiently restore normal biomechanics to the ACL-deficient knee, protect the restored ACL, or enhance long-term patient outcomes, according to biomechanical and clinical research (81).…”
Section: Preoperative Phasementioning
confidence: 99%